Coeducation and gender: Concepción and practices of Physical Education teachers in Chile - Pérez Norambuena, Samuel (2024)
The topic of gender in physical education plays an important role in the teaching-learning process and has been influenced by a technical-sport bias that hides the practice of specialized teachers in this area. The transition from segregated to coeducational classes often does not reflect the true purpose of this inclusion. Therefore, this study sought to understand how physical education teachers address the issue of gender in their coeducational classes. A qualitative methodology was used, analyzing semi-structured interviews with 7 physical education teachers who teach mixed classes, with the help of Nvivo version 14 program. Among the main findings, certain stereotypes were identified that reflect the conceptions of physical education and the educational practices of the teachers, where certain levels of gender segregation and discrimination still persist. These stereotypes, although subtle, have a significant impact on the way physical education is understood and taught, perpetuating traditional gender roles and limiting equitable student participation.